2021
DOI: 10.1002/jcp.30414
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐Adipose Tissue Crosstalk: Role of Adipose Tissue Derived Extracellular Vesicles in Bone Diseases

Abstract: Bone is a metabolically active organ that undergoes constant remodeling throughout life. A failure of this process leads to pathological destructive bone diseases such as osteoporosis, rheumatoid arthritis, and osteoarthritis. Studies of the interplay between adipose tissue and bone system, have revealed that adipose tissue disorders (e.g. obesity) strongly influence the development of bone diseases. Adipokines secreted by adipose tissue play important roles in the crosstalk between bone and adipose tissue. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…In this context, it is possible to infer that miR-15b-5p, an upregulated miRNA in circulating adipocyte-derived EVPs here reported, can be involved with those findings of CCND1, given that this cyclin was strongly reduced in muscle stem cells from 20 to 22-months-old male mice, impairing myoblast proliferation and differentiation, including in response to regenerative conditions ( Brett et al, 2020 ). In addition, Zhang et al (2021) suggested the role of adipose tissue-derived EVPs cargo on bone remodeling events. Taken that tibia from 19-month-old aged female mice showed downregulated cyclins, CCNA2, CCND3, CCNE1-2, the upregulation of miRNA-15b-5p, miR-24-3p, and miR-92b-3p (and consequent silencing of cyclins) can be related, at least in part, to declines in bone mass and fracture in older adults, in the context of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is possible to infer that miR-15b-5p, an upregulated miRNA in circulating adipocyte-derived EVPs here reported, can be involved with those findings of CCND1, given that this cyclin was strongly reduced in muscle stem cells from 20 to 22-months-old male mice, impairing myoblast proliferation and differentiation, including in response to regenerative conditions ( Brett et al, 2020 ). In addition, Zhang et al (2021) suggested the role of adipose tissue-derived EVPs cargo on bone remodeling events. Taken that tibia from 19-month-old aged female mice showed downregulated cyclins, CCNA2, CCND3, CCNE1-2, the upregulation of miRNA-15b-5p, miR-24-3p, and miR-92b-3p (and consequent silencing of cyclins) can be related, at least in part, to declines in bone mass and fracture in older adults, in the context of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of E2F3 induced cell cycle arrest by inhibiting the induction of S phase (Leone et al, 1998). Moreover, bioinformatic analyses, functional clustering analysis, pathway enrichment, gene network interactions, and transcription factor of transcriptomic changes in tibia from old mice compared with young ones revealed "cell cycle" as a crucial category, including terms as organ development, cell cycle checkpoints and regulation of programmed cell death, chromatin assembly, DNA damage checkpoint, regulation of cell cycle, apoptosis, and regulation of metabolic process (Zhang et al, 2021). On the other hand, miRNA profiling in circulating EVPs can reflect the tissue and cellular miRNA signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the therapeutic use of EVs from ASCs in the clinic is also attractive and scientifically supported by the results obtained through a wide variety of experimental pathological conditions, ranging from kidney transplantation to inflammatory bone diseases and tissue regeneration [94][95][96][97].…”
Section: Advantages and Disadvantages Of The Potential Use Of Asc-der...mentioning
confidence: 99%
“…Furthermore, it must be considered that EVs carry only a fraction of the molecules produced by the cells of origin, which are selected for specific purposes such as supplying neighboring/distal cells with energetically, biochemically or enzymatically useful materials, as well as nucleic acids, which can alter the expression of the target genes. This can be an advantage but also as a disadvantage, considering the restriction in the range of products donated by EVs compared with entire MSCs [96], and also implies that the therapeutic dose and efficacy of EVs must still be clearly defined. Furthermore, EVs can home in on certain tissues depending on their source tissue, which would be mainly useful in the case of EV use for targeted drug delivery [33], although it is not clear how extensive this homing ability is.…”
Section: Disadvantagesmentioning
confidence: 99%
“…Kian F Eichholz et al demonstrated that osteocytes can be mechanically activated to secrete EVs to regulate mesenchymal stem cell differentiation [ 48 ]. EVs not only play a therapeutic role in other diseases, but also play an important role in osteoporosis [ 28 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Based on Xin Qi et al, exosomes secreted by human-induced pluripotent stem cell-derived mesenchymal stem cells repair critical-sized bone defects through enhanced angiogenesis and osteogenesis in osteoporotic rats [ 57 ].…”
Section: The Potential Therapeutic Effects Of Evs In Osteoporosismentioning
confidence: 99%